Influence of Sulfur Incorporation into Nanoporous Anodic Alumina on the Volume Expansion and Self-Ordering Degree - Minguez Bacho, Ignacio; Rodriguez-Lopez, S.; Climent, A.; Fichou, Denis; Vazquez, Manuel; Hernandez-Velez, Manuel Mhv (Journal of Physical Chemistry C, 2015)
Self-ordering degree of anodic alumina nanopores is related to the volume expansion of the aluminum oxide. However, little is known about how the ionic species derived from electrolyte affect parameters inducing self-ordering of the nanopores. The influence of sulfur incorporation into nanoporous anodic aluminum oxide (AAO) films on volume expansion and self-ordering degree has been investigated under potentiostatic conditions (14-25 V) in different sulfuric acid electrolytes (3-20 wt %), the average current densities of each anodization being in the range of 0.1-10 mA cm(-2). Rutherford backscattering spectroscopy (RBS) reveals that the incorporation of sulfur species into AAO, as well as the volume expansion factor (VEF), follows a logarithmic dependence on the average current density regardless of the applied voltage and sulfuric acid concentration. The relationship between volume expansion and the S/Al ratio is linear for each concentration of acid in the electrolyte. Furthermore, self-ordering regimes are also revealed for each acid concentration at VEF in the range of 1.50-1.66. We suggest that plasticity, enhanced by sulfur incorporation, counterbalances the high mechanical stress generated by volume expansion, thus inducing new self-ordering regimes. These new regimes are dependent not only on VEF but also on a subtle equilibrium between stress and plasticity of the nanoporous AAO films.